Alterations in serum proteins and immunoglobulins in diarrhoeic buffalo calves - JOSHI, V B; SAINI, S S; SODHI, S S (The Indian Journal of Animal Sciences, 2013)
Diarrhoeic buffalo calves (14) of 1-2 weeks of age had lower serum protein, IgG and IgM cuucentrations on the first day of onset of diarrhoea than the non-diarrhoeic apparently healthy calves (23). Calves recovered from diarrhoea within 10 days after treatment with phthalyl sulphathiazole, pectin and kaolin, and had significantly lower (P